Characterization of neuromuscular performances in adults with late-onset Pompe disease: A control case cross-sectional study - Maulet, Théo; Bonnyaud, Céline; Laforêt, Pascal; Cattagni, Thomas (Neuromuscular disorders : NMD, 2023)
•Maximum strength was the only neuromuscular performance affected in Pompe disease.•Our study highlights a proximal-distal gradient in muscle weakness intensity.•The weakest muscles were the hip extensors followed by hip abductors and abductors.•Instrumented assessment of the weakest muscles is essential.•Neural and muscular fibers factors of aLOPD are as functional as those of controls. Adults with late-onset Pompe disease (aLOPD) are characterized by muscular contractile tissue deterioration. However, their neuromuscular performances are poorly known. We aimed to compare maximal muscle strength, activation, explosive strength and neuromuscular fatigue between aLOPD and controls. We studied 20 aLOPD and 20 matched controls. Isometric maximum voluntary contraction (MVC) torque was obtained for the hip, knee and ankle muscles. The voluntary activation level (VAL) during knee extensor MVC was assessed using interpolated twitch technique. Explosive strength was evaluated for knee and ankle muscles through the rate of torque development (RTD) during fast contractions. Neuromuscular fatigue was measured during a 30-second contraction of knee flexors and extensors. All muscle MVC torques were significantly lower in aLOPD than controls (p <0.05). The weakest muscles were the hip extensors followed by hip abductors and abductors. Raw value of RTD was lower in aLOPD for the majority of muscles (p <0.05). No intergroup differences were reported for normalized RTD, VAL and neuromuscular fatigue (p-values> 0.05). Our study shows that maximal strength was the only neuromuscular characteristic affected in aLOPD with a proximal-distal intensity gradient. This suggests that the surviving muscle tissue of aLOPD is as functionally efficient as that of control individuals.